2021
DOI: 10.3390/jpm11050389
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ATM and BRCA1 Predicts Poor Outcome in Head and Neck Cancer: Implications for ATM-Targeted Therapy

Abstract: ATM and BRCA1 are DNA repair genes that play a central role in homologous recombination repair. Alterations of ATM and BRCA1 gene expression are found in cancers, some of which are correlated with treatment response and patient outcome. However, the role of ATM and BRCA1 gene expression in head and neck cancer (HNC) is not well characterized. Here, we examined the prognostic role of ATM and BRCA1 expression in two HNC cohorts with and without betel quid (BQ) exposure. The results showed that the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Previously, we found that the ATM inhibitor (ATMi) KU55933 activated interferon pathways in cancer cells (Figure 2A) [29]. Here, gene expression profiling and GSEA demonstrated that KU55933 also induced the interferon response in CDDP-R cancer cells (Figure 2B).…”
Section: The Interferon Response Was Activated Upon Atm Inhibition Bu...supporting
confidence: 53%
See 2 more Smart Citations
“…Previously, we found that the ATM inhibitor (ATMi) KU55933 activated interferon pathways in cancer cells (Figure 2A) [29]. Here, gene expression profiling and GSEA demonstrated that KU55933 also induced the interferon response in CDDP-R cancer cells (Figure 2B).…”
Section: The Interferon Response Was Activated Upon Atm Inhibition Bu...supporting
confidence: 53%
“…Total RNA from KU55933-treated HEp-2 (10 µM, 24 h) and HB8 (10 and 20 µM, 24 h) cells was harvested using Tri-reagent (Sigma) for the analysis of gene expression profiles (Human OneArray Plus HOA 7.1, Phalanx Biotech, Taiwan), as described in our paper [29]. Transcriptome data sets of normal human dermal fibroblasts treated with KU60019 and lung cancer cells resistant to cisplatin were retrieved from NCBI GEO with accession numbers GSE178115 and GSE21656, respectively.…”
Section: Transcriptomic Data Sets and Gene Set Enrichment Analysis (G...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the expression of DNA repair genes ATM and BRCA1 was suppressed in betel nut-associated HNSCC due to arecoline. Low expression of either ATM or BRCA1 was related to poor overall survival and presented as an independent prognostic factor ( 31 ). Here, for the first time, we screened thirteen DEGs based on arecoline-related OSCC samples from the GSE139869 gene array and TCGA-OSCC dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Another key mechanism by which ATM and ATR inhibitors selectively enhance tumor cell inactivation when combined with IR) may be through the inducing of senescence (142). A recent study showed that the ATM inhibitor KU55933 induces apoptotic signaling and potentiates cisplatin-induced cytotoxicity (45). GSK63541A, a novel ATM inhibitor, has been shown to have a highly selective radiosensitization activity that is superior to cisplatin and cetuximab (115).…”
Section: Atr and Atm Inhibitorsmentioning
confidence: 99%